2001
DOI: 10.1056/nejm200101043440103
|View full text |Cite
|
Sign up to set email alerts
|

The Pathogenesis of Acute Pulmonary Edema Associated with Hypertension

Abstract: In patients with hypertensive pulmonary edema, a normal ejection fraction after treatment suggests that the edema was due to the exacerbation of diastolic dysfunction by hypertension--not to transient systolic dysfunction or mitral regurgitation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
242
3
20

Year Published

2002
2002
2018
2018

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 641 publications
(273 citation statements)
references
References 16 publications
8
242
3
20
Order By: Relevance
“…However, to provide additional information on the potential beneficial effects of serelaxin in these groups of patients, echocardiograms are obtained during the index hospitalization in RELAX‐AHF‐2. The timing of the echocardiograms was not specified, since a prior study suggested that left ventricular function does not change significantly in these types of AHF patients33 and it would be undesirable to have the echocardiogram interfere with randomization and initiation of study drug.…”
Section: Discussionmentioning
confidence: 99%
“…However, to provide additional information on the potential beneficial effects of serelaxin in these groups of patients, echocardiograms are obtained during the index hospitalization in RELAX‐AHF‐2. The timing of the echocardiograms was not specified, since a prior study suggested that left ventricular function does not change significantly in these types of AHF patients33 and it would be undesirable to have the echocardiogram interfere with randomization and initiation of study drug.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism of sudden apical tenting remains therefore to be elucidated. None of the patients presented with marked hypertension during the acute episodes [18]. Systematic triggering of MR by methylergonovine injection, chest pain and ST segment depression in patient 3 during the regurgitation, rapid reversibility with nitroglycerine and methylergonovine-induced perfusion defect on scintigraphy during the regurgitation phase favor its ischemic origin.…”
Section: Discussionmentioning
confidence: 99%
“…Many patients with HFpEF have concomitant systolic dysfunction abnormalities, particularly in the long axis [4,21,28,41], which may limit their tolerated systolic pressures. Beyond the profound structural changes underlying diastolic dysfunction and volume loading, limited tolerance to systolic pressures may provide additional mechanistic information on hypertensive pulmonary edema [15,17].…”
Section: Discussionmentioning
confidence: 99%